Diagnostic value of apoptosis biomarkers in severe sepsis-A pilot study - Chu, C-M; Kao, K-C; Huang, S-H; Chuang, D-Y; Wu, H-P (Cellular and Molecular Biology, 2016)
Severe sepsis is associated with significant mortality and massive immune cell lose, or apoptosis. It is unclear whether plasma apoptosis biomarkers could be used as a diagnostic test for severe sepsis. Forty patients with severe sepsis and 35 healthy controls were enrolled. The percentage and apoptosis of monocytes and lymphocytes were detected by flow cytometric analysis. Plasma levels of tumor necrosis factor (TNF)-Î±, soluble TNF receptor (sTNFR), soluble Fas (sFas), Fas ligand (FasL), caspase-1, and procalcitonin (PCT) were measured. Plasma caspase-1 level was positively correlated with CD4 lymphocyte apoptosis in controls and patients, and with CD8 lymphocyte apoptosis in all subjects. Plasma FasL level was negatively correlated with CD4 and CD8 lymphocyte apoptosis in all subjects. The sFas/FasL ratio was positively correlated with CD4 and CD8 lymphocyte apoptosis and negatively with monocyte apoptosis in all subjects. Compared with PCT, caspase-1, FasL, and sFas/FasL ratio had better negative predictive value and likelihood ratio for a negative test. PCT had better positive predictive value and likelihood ratio for a positive test. This work demonstrated caspase-1, FasL, and sFas/FasL ratio could be candidates for diagnosis of severe sepsis and their diagnostic value was not inferior to that of PCT.